Program Mindfulness Based Stress Reduction untuk Menurunkan Kecemasan pada Individu dengan Penyakit Jantung Koroner - Munazilah Munazilah; Nida Ul Hasanat (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
This study was conducted in individuals with chronic diseases, namely coronary heart disease (CHD). Individuals with CHD experience changes in various aspects of life that create stress in the form of anxiety. The MBSR program can improve the parasympathetic nervous system, reduce the production of adrenaline and epinephrine so that symptoms of stress and anxiety can decrease. The purpose of this study was to determine the effect of the Mindfulness-Based Stress Reduction (MBSR) program on reducing anxiety in individuals with CHD. The research method used a quasi-experiment with the design of the one group pretest-posttest design. Data analysis with Sign-Rank Wilcoxon Test non-parametric test. The results showed that there was a significant decrease in anxiety in CHD individuals with a value of Z = -2.023 and p = 0.043 (p <0.05). Based on these results, the MBSR program has been proven to reduce individual anxiety with CHD.